Massive tubular ectasia of the rete testes in a patient with Marfan syndrome - Ashley Lee; Su-Tong Low; Steve McCombie; Dickon Hayne (Urology Case Reports)
This case study explores massive tubular ectasia of the rete testes in a patient with Marfan syndrome. Marfan syndrome is a connective tissue disorder and has no known association with tubular ectasia in published research. Despite the unclear pathophysiology of tubular ectasia, potential causes include mechanical obstruction and congenital deformity. The patient, a male in his 40s, presented with bilateral testicular pain and swelling up to a volume of 200 cc over two years. Tubular ectasia was diagnosed on ultrasound and MRI, no obstructive aetiology was identified. Initial conservative management was chosen, but further enlargement led to reconsideration of treatment options.